KRITIK TERHADAP PEMASARAN BANK SYARIAH (PENDEKATAN EKSPERIENTAL MARKETING) - Rinda Asytuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
This study examines the idea of Bernard Schmitt, ‘experiential marketing’, on Islamic banks that are operating side by side with conventional banks. This marketing is a concept that integrates elements of emotions, logic, and general thought processes to connect with the consumer. The goal of experiential marketing is to establish the connection in such a way that the consumer responds to a product offering based on both emotional and rational response levels. Via